MANTLE FLUIDS AND NOBLE GAS ISOTOPIC COMPOSITIONS OF PERIDOTITIC OLIVINES IN CENOZOIC BASALTS FROM EASTERN NORTH CHINA - Tang H.Y.; Zheng J.P.; Yu C.M. (My University, 2007)
Compositions of the fluids and noble gases in the peridotitic olivines from the Cenozoic basalts in Shanwang and Qixia (Shandong Province) and Hebi (Henan Province) areas were measured by heating-bursting and high temperature melting extraction method, respectively. The results show that a harzburgite sample from Hebi has 3He/4 He ratio of 0.778 Ra and air-like heavy noble gases isotopic compositions. The fluids from those fertile samples, which represent the newly accreted lithospheric mantle, are mainly composed of reducing gases and have CO2/3 He, N2/3He, N2/Ar ratios of (0.62 ∼ 4144) × 109, (2631 ∼ 64482) × 106, 269 ∼ 73467, respectively. These values are significantly different from those of typical mande-derived fluids but similar to crustal fluids, reflecting the excess of carbon and nitrogen in these fluids. Such fluids compositions can be interpreted to mix among air, mantle, and crustal components, further reflecting the contamination of atmosphere and crustal materials with organic components in the upper mantle beneath the studied areas. Additionally, all of these fertile samples have air-like Ne, Ar, Kr, Xe isotopes, reflecting the comprehensive atmospheric component contamination in the upper mantle. However, the Shanwang and Qixia samples have 3He/4 He ratios of (2.91 ∼ 3.07) Ra and (1.79 ∼ 4.01) Ra, respectively, both of which are higher than the atmospheric value but lower than the MORB ratio and reflect the enriched nature of the sub-continental mantle, whereas the Hebi ones are characterized by MORB-like 3He/4 He ratios of (7.03 ∼ 7.05) Ra. Such fluids and noble gases compositions indicate that the newly accreted lithospheric mantle beneath the eastern North China could be MORB-type depleted mantle with crustal components, and much more crustal components are contained in the eastern margin than in the central of the North China, further suggesting the existence of oceanic depleted mantle with the involvement of the subducted Pacific oceanic materials beneath the eastern North China.